Analysis of the Implementation of the Wadiah Contract System and Financial Report Performance on Bank Management Strategy (Case Study of Indonesian Sharia Banks for the 2021-2023 Period) - nindi; Sulfarid; Muhamad Nurman (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of the wadiah contract system and financial report performance on the management strategy of Bank Syariah Indonesia (BSI). A qualitative descriptive approach was employed using secondary data, including financial reports, regulatory documents, and academic literature. The results show that the wadiah contract plays a significant role in third-party fund collection through savings and checking products that are free from interest elements. This contract contributes to the bank’s cost of fund efficiency due to the absence of profit-sharing obligations and supports liquidity enhancement. Furthermore, BSI’s financial performance, reflected in ROA, CAR, and FDR indicators, demonstrates stable and sound managerial capacity. The integration of sharia-based contract practices and strong financial performance strengthens BSI’s position in the competitive Islamic banking industry. This study enriches the discourse on the integration of sharia principles into sustainable bank financial management strategies.